The influence innovation strategy and company’s financial performance mediated by intellectual capital and internal process performance - Lintang Venusita, Hariyati, (Opción, 2019)
This research examines the influence of innovation strategy and the company’s financial performance through mediation between intellectual capital and internal process performance. This research is quantitative research on the explanatory level. The data is collected through questionnaires. The research respondent is the manager or owner of the business unit in the Manufacturing Company in East Java. The research result shows that the intellectual capital and internal process performance mediates partially the relation between innovation strategy and financial performance. In conclusion, the relation between innovation strategy and financial performance is mediated partially by the intellectual capital an internal process performance.